SIRT5-mediated PRKAA2 succinylation ameliorates apoptosis of human placental trophoblasts in hypertensive disorder complicating pregnancy - Feifei Ren; Mo Yang; Guangman Liu; Yuyan Qi; Aijie Li; Jia Li; Lili Zheng (Clinical and Experimental Hypertension)
Purpose Hypertensive disorder complicating pregnancy (HDCP) is a serious clinical disorder syndrome during pregnancy. This study aims at finding novel targets for HDCP therapy.Methods HDCP-related mRNAs were firstly screened out and subjected to gene enrichment analysis. We chose protein kinase AMP-activated catalytic subunit alpha 2 (PRKAA2) as the research object. Thirty-nine HDCP patients at 32 to 40 weeks of gestation were selected as the HDCP group, and 39 normal controls who received cesarean section delivery at 37–42 weeks of pregnancy were enrolled in this study. Chorionic villi samples were collected within 30 min of delivery. The apoptosis of isolated placental trophoblasts was monitored to investigate the regulatory role of PRKAA2.Results PRKAA2 expression was further proven to be enhanced in the placental tissues of HDCP patients compared with that of normal puerpera. Subsequently, the results of flow cytometry analysis and western blot indicated that PRKAA2 overexpression accelerated primary placental cell apoptosis, while its knockdown attenuated cell apoptosis. Mechanistically, we determined that the level of PRKAA2 succinylation was elevated in the placental tissue of HDCP patients. Through in vitro succinylation assay and mutagenesis, we confirmed that sirtuin 5 (SIRT5) interacts with PRKAA2 at K69 and K260 to induce PRKAA2 desuccinylation. SIRT5 regulated primary HDCP cell apoptosis through PRKAA2. Finally, the animal study revealed that PRKAA2 elevates the systolic blood pressure of HDCP rat model.Conclusion Our findings indicated that SIRT5-mediated PRKAA2 succinylation modulates placental cell apoptosis in HDCP, suggesting that PRKAA2 is a potential therapeutic target for HDCP treatment.